Integration of Sustainable Entrepreneurship and Green Economy to Improve Food Security in Malang City - Usmanisa, Maslikhatur Rodiyah Sita; Fitria Dina Riana; Silvana Maulidah (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
As an initiative to move away from conventional agriculture and increase food production, the Badan Keamanan Pangan (BKP) since 2010 has implemented the Sustainable of Kawasan Rumah Pangan Lestari (KRPL) or currently known as the Yard Utilization Program. This study aims to explore more deeply how sustainable entrepreneurship and green economy can synergize to improve food security in Malang City, with moderation in the role of institutions in the yard utilization program. The existence of entrepreneurship that prioritizes environmentally friendly practices is also an asset for green transformation, with the existence of sustainable entrepreneurship, it can be interpreted that agricultural activities are one of the efforts to support green transformation. The data results from the research were analyzed using the SEM-PLS tool with the WarpPLS 8.0 approach. Based on the research conducted, it can be concluded that through entrepreneurship created from the sustainable yard utilization program by taking into account environmental, social and economic aspects, it was revealed that areas that initially had a medium food insecurity status experienced an increase in food security status.